Books on Prescription - community‐based health initiative to increase access to mental health treatment: an evaluation - Sophie Carty; Louise Thompson; Sarah Berger; Katie Jahnke; Rebecca Llewellyn (Elsevier, 2016)
Abstract Objective: To evaluate the implementation of a regional Books on Prescription (BoP) programme. Methods: Seven data collection pathways were used to provide indicators of program implementation, utilisation, acceptability and reach. Results: BoP is seen by prescribers, librarians and consumers as a valuable mental health resource. Key areas for improvement were identified: booklist literacy level and breadth of topic area; confidentiality; program promotion; and prescriber/librarian training. Conclusions: Recommendations are made regarding the improvement of programme acceptability, accessibility and assessment. Implications: The establishment of a national BoP scheme would facilitate sustainable and consistent methods for BoP promotion and assessment. The authors hope this evaluation is a step towards actualising this goal.